PENGARUH PAJAK DAERAH TERHADAP PENDAPATAN ASLI DAERAH PROVINSI JAWA BARAT - Syahrial, Syahrial (Universitas Logistik dan Bisnis Internasional, 2025)
West Java Province in an effort to improve people's welfare, the West Java Provincial Government is trying to increase Regional Income (PD), one of which is through taxes. In the regional income report of West Java Province, local taxes are sourced from motor vehicle taxes, motor vehicle fuel taxes, and cigarette taxes with text data types. This thesis aims to determine and analyze the effect of local taxes on local revenue in West Java province for the 2020-2021 period. The data analysis technique used in this research is data normality test, product moment correlation analysis, simple linear regression analysis, coefficient of determination analysis, and t-test. From the results of this study indicate that local taxes have a significant effect on local revenue in the province of West Java.